Synergistic effects of drought and deforestation on the resilience of the south-eastern Amazon rainforest - Staal, Arie; Dekker, Stefan C.; Hirota, Marina; van Nes, Egbert H. (Ecological complexity, 2015)
•A simple model is presented with alternative stable states in tree cover.•The model was fitted to data of tree cover from South America.•The effects of deforestation and drought on regime shifts from forest to savanna in the south-eastern Amazon rainforest were analyzed.•Together, deforestation and drought cause up to 6.6 times as many locations to shift than separately. The south-eastern Amazon rainforest is subject to ongoing deforestation and is expected to become drier due to climate change. Recent analyses of the distribution of tree cover in the tropics show three modes that have been interpreted as representing alternative stable states: forest, savanna and treeless states. This situation implies that a change in environmental conditions, such as in the climate, could cause critical transitions from a forest towards a savanna ecosystem. Shifts to savanna might also occur if perturbations such as deforestation exceed a critical threshold. Recovering the forest would be difficult as the savanna will be stabilized by a feedback between tree cover and fire. Here we explore how environmental changes and perturbations affect the forest by using a simple model with alternative tree-cover states. We focus on the synergistic effects of precipitation reduction and deforestation on the probability of regime shifts in the south-eastern Amazon rainforest. The analysis indicated that in a large part of the south-eastern Amazon basin rainforest and savanna could be two alternative states, although massive forest dieback caused by mean-precipitation reduction alone is unlikely. However, combinations of deforestation and climate change triggered up to 6.6 times as many local regime shifts than the two did separately, causing large permanent forest losses in the studied region. The results emphasize the importance of reducing deforestation rates in order to prevent a climate-induced dieback of the south-eastern Amazon rainforest.